2022
DOI: 10.3389/fnins.2022.996368
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation-related genes and immune infiltration landscape identified in kainite-induced temporal lobe epilepsy based on integrated bioinformatics analysis

Abstract: BackgroundTemporal lobe epilepsy (TLE) is a common brain disease. However, the pathogenesis of TLE and its relationship with immune infiltration remains unclear. We attempted to identify inflammation-related genes (IRGs) and the immune cell infiltration pattern involved in the pathological process of TLE via bioinformatics analysis.Materials and methodsThe GSE88992 dataset was downloaded from the Gene Expression Omnibus (GEO) database to perform differentially expressed genes screening and weighted gene co-exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Studies show that in ammation is a major factor in epilepsy 32,33 . For instance, a study discussed the role of P2X7 receptors in epilepsy and neuroin ammation, particularly their expression on various cells in the brain and their involvement in the in ammatory process during epileptic seizures 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that in ammation is a major factor in epilepsy 32,33 . For instance, a study discussed the role of P2X7 receptors in epilepsy and neuroin ammation, particularly their expression on various cells in the brain and their involvement in the in ammatory process during epileptic seizures 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have applied a similar method of investigation before. A recent study investigated inflammation‐related genes and the immune cell infiltration patterns involved in the pathological processes of TLE via bioinformatics analysis 66 …”
Section: Limitationsmentioning
confidence: 99%
“…Previous study has demonstrated that Jun is immune-related biomarker for TLE [24]. JUN has also been identi ed as a diagnostic of Alzheimer's Disease potential ferroptosis-related biomarkers [25].…”
Section: Correlation Of Ferroptosis-related Hub Gene With Immune Cellsmentioning
confidence: 99%